2020
DOI: 10.1115/1.4048957
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Data Fusion Method for In Situ Porosity Detection in Laser-Based Additive Manufacturing

Abstract: Laser-Based Additive Manufacturing (LBAM) provides unrivalled design freedom with the ability to manufacture complicated for a wide range of engineering applications. Melt pool is one of the most important signatures in LBAM and is indicative of process anomalies and part defects. High-speed thermal images of the melt pool captured during LBAM make it possible for in-situ melt pool monitoring and porosity prediction. This paper aims to broaden current knowledge of the underlying relationship between process an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…One challenge of integrating PIML into multimodal sensor data is matching modalities of different sensors. In one way, Guo et al appended finite element analysis (FEA)-simulated data to a convolutional neural network (CNN) model that incorporated thermal images from sensors [22]. In another way, Gawade et al matched the FEA-simulated melt pool data to thermal melt pool images by similar location and time [23].…”
Section: In Situ Monitoring Techniques In Lmdmentioning
confidence: 99%
See 2 more Smart Citations
“…One challenge of integrating PIML into multimodal sensor data is matching modalities of different sensors. In one way, Guo et al appended finite element analysis (FEA)-simulated data to a convolutional neural network (CNN) model that incorporated thermal images from sensors [22]. In another way, Gawade et al matched the FEA-simulated melt pool data to thermal melt pool images by similar location and time [23].…”
Section: In Situ Monitoring Techniques In Lmdmentioning
confidence: 99%
“…Khanzadeh et al used morphological characteristics of the melt pool boundary to investigate the relationship between the melt pool characteristics and the defect occurrence in an as-built AM part [24]. Tian et al developed a deep learningbased data fusion method for in situ porosity detection in laser-based AM [22]. Yang et al developed a CNN model to investigate how the melt pool can be characterized in real time for feedback control of a laser powder bed fusion AM process [25].…”
Section: Machine Learning-based Models In Lmdmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Recently, several methods have been designed for real-time porosity inspection during AM by online monitoring of melt-pool features (e.g., temperature, geometry, and radiation intensity). 2226 Although these methods can examine porosity with a high accuracy, a large amount of iterative testing is required to establish a new relationship between the melt pool features and porosity once the target AM process or material is changed. In addition, the authors proposed a femtosecond laser-based transient thermoreflectance (TTR) measurement system for in situ porosity inspection.…”
Section: Introductionmentioning
confidence: 99%
“…Although this approach showed great achievements in abnormality detection, the manual selection of features and thresholds need to show generalizability to more complex and non-linear problems. On the other hand, Qi et al (Tian et al, 2021) suggested DL based feature extraction for a metal AM machine. Their setup consisted of a pyrometer working alongside a thermal camera and a 3D CT scan machine.…”
Section: Introductionmentioning
confidence: 99%